A Study on the Relationship Between Safety Promotion, Safety Communication and Safety Performance Among ERL Maintenance Support Sdn Bhd Employees - Mezlan, Yaacob (2012)
Workplace safety is about preventing injury and illness to employees and volunteers in the workplace. Organization must actively manage safety in order to achieve high levels of safety performance. High levels of safety performance require an effective method for managing and controlling safety that is specifically focused on the safety promotion and safety communication of the organization. This study is to determine the influence of safety promotion and safety communication in respect to their relationship for improvement of safety performance. This study was conducted using questionnaires to selected departments with 150 staff at ERL Maintenance Support Sdn. Bhd., (E-MAS) Sepang, Selangor Darul Ehsan. Data gathered will be analyzed through the SPSS version19.1. All independent variables will be measured on the employees perception towards enhancement safety performance as the determinants (dependent variable). Finally, the finding of the study presented that safety promotion and safety communication are significantly relationship with safety performance. The conclusion of the findings found that the safety promotion activities and proper safety communication had strong influence as instruments to enhance safety performance of organization.